Fabrication of interdigitated high-performance zinc oxide nanowire modified electrodes for glucose sensing - R. Haarindraprasad; Uda Hashim; Subash C.B. Gopinath; Veeradasan Perumal; Wei-Wen Liu; S.R. Balakrishnan (Elsevier, 2024)
Analytica Chimica Acta Volume 925, 21 June 2016, Pages 70-81